2015
DOI: 10.1590/01000683rbcs20140718
|View full text |Cite
|
Sign up to set email alerts
|

Carbono Orgânico Total E Agregação Do Solo Em Sistema De Plantio Direto Agroecológico E Convencional De Cebola

Abstract: reSUmo decorrente dos sistemas de manejo empregados no solo, como o sistema de preparo convencional (SPC) versus o sistema de plantio direto de hortaliças (SPDH), modificações nos atributos edáficos ocorrem; por exemplo, nos índices de agregação do solo e seu teor de carbono orgânico total (COT). Objetivaram-se quantificar os teores de COT e avaliar os índices de agregação do solo e a distribuição dos agregados por classes de diâmetro sob cultivo de cebola em SPdH e SPC, comparados a uma área de mata adjacente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
36

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 36 publications
3
71
0
36
Order By: Relevance
“…However, Loss et al (2015) showed significant differences in aggregation between soils managed under CTS and NTSH, especially in the formation of macroaggregates (8.00 mm > Ø ≥ 2.0 mm). Thus, the use of undisturbed soil samples is important to better assess the effects of management systems in evaluations of HS contained in aggregates of the soil.…”
Section: Nitrogen and Humic Substances In Onion Under No-tillage And mentioning
confidence: 91%
See 4 more Smart Citations
“…However, Loss et al (2015) showed significant differences in aggregation between soils managed under CTS and NTSH, especially in the formation of macroaggregates (8.00 mm > Ø ≥ 2.0 mm). Thus, the use of undisturbed soil samples is important to better assess the effects of management systems in evaluations of HS contained in aggregates of the soil.…”
Section: Nitrogen and Humic Substances In Onion Under No-tillage And mentioning
confidence: 91%
“…The experiment was carried out in a Humic Cambisol (Inceptisol) of clay loam texture (Loss et al, 2015), with 380 g kg -1 clay, 200 g kg -1 silt and 420 g kg -1 sand. The area was cultivated with onion in CTS (plowing, harrowing and scarification) for about 20 years until 1996.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations